2010
DOI: 10.1097/aln.0b013e3181ebdaf9
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Pain

Abstract: Cigarette smoke, which serves as a nicotine delivery vehicle in humans, produces profound changes in physiology. Experimental studies suggest that nicotine has analgesic properties. However, epidemiologic evidence shows that smoking is a risk factor for chronic pain. The complex relationship between smoking and pain not only is of scientific interest, but also has clinical relevance in the practice of anesthesiology and pain medicine. This review will examine current knowledge regarding how acute and chronic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(133 citation statements)
references
References 214 publications
(208 reference statements)
5
124
4
Order By: Relevance
“…This is consistent with the idea that CWP and CRP may have different underlying aetiologies 7. For example, some studies have suggested that nicotine may alter pain regulatory mechanisms (eg, potential alteration of pain processing or cause structural changes to other systems) which might have long-term consequences for painful chronic conditions 29. The associations between lifetime smoking and CWP were only partially attenuated after adjustment for a range of factors including sex, socioeconomic position, body size, other health behaviour, long-standing illness and symptoms of anxiety and depression.…”
Section: Discussionsupporting
confidence: 84%
“…This is consistent with the idea that CWP and CRP may have different underlying aetiologies 7. For example, some studies have suggested that nicotine may alter pain regulatory mechanisms (eg, potential alteration of pain processing or cause structural changes to other systems) which might have long-term consequences for painful chronic conditions 29. The associations between lifetime smoking and CWP were only partially attenuated after adjustment for a range of factors including sex, socioeconomic position, body size, other health behaviour, long-standing illness and symptoms of anxiety and depression.…”
Section: Discussionsupporting
confidence: 84%
“…These findings suggest that although smoking, pain, depression, and opioid use appear to be interrelated, greater levels of depression among smokers may not be sufficient to account for why they needed higher opioid dosages. It is possible that smoking and opioid use demonstrate unique associations (e.g., above-and-beyond the influence of depression) due to complex nicotine-opioid interactions that can result in cross-tolerance and/or sensitization to the rewarding effects of opioid medications (Shi, Weingarten, et al, 2010; Vihavainen, Piltonen, Tuominen, Korpi, & Ahtee, 2008). …”
Section: Anxiety and Depression In Bidirectional Pain–smoking Relationsmentioning
confidence: 99%
“…Second, withdrawal severity is a hypothesized mechanism by which smokers may experience greater pain during periods of abstinence (e.g., Allen et al, 2000). Third, researchers have suggested that smokers who experience greater pain and pain-related negative affect during a quit attempt may return to smoking, in part, to alleviate increased pain sensitivity (Ditre et al, 2011; Shi, Weingarten, et al, 2010). …”
Section: Implications For Smoking Cessationmentioning
confidence: 99%
“…Although animal models have consistently demonstrated acute pain-inhibitory effects of nicotine/tobacco administration for over 80 years [19; 44], human experimental studies have generated mixed and somewhat contradictory findings [22; 70]. Indeed, the question of whether nicotine may decrease sensitivity to pain in humans has been a topic of empirical debate since the effects of smoking on human pain reactivity were first examined in 1973 [45; 58].…”
Section: Introductionmentioning
confidence: 99%